2016
DOI: 10.1190/geo2015-0345.1
|View full text |Cite
|
Sign up to set email alerts
|

Time-lapse full-waveform inversion with ocean-bottom-cable data: Application on Valhall field

Abstract: Knowledge of changes in reservoir properties resulting from extracting hydrocarbons or injecting fluid is critical to future production planning. Full-waveform inversion (FWI) of time-lapse seismic data provides a quantitative approach to characterize the changes by taking the difference of the inverted baseline and monitor models. The baseline and monitor data sets can be inverted either independently or jointly. Time-lapse seismic data collected by ocean-bottom cables (OBCs) in the Valhall field in the North… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…From top to bottom, the depth slices intersect glacial sand channel deposits, a wide low-velocity zone intersected by scrapes left by drifting icebergs on the paleo-seafloor, the gas cloud and the base cretaceous reflector, respectively. These structures have been well documented by FWI in Sirgue et al (2010), Barkved et al (2010), Operto et al (2015), Yang et al (2016a) and Figure 11. FWI perturbation models (Q).…”
Section: Modelssupporting
confidence: 53%
See 1 more Smart Citation
“…From top to bottom, the depth slices intersect glacial sand channel deposits, a wide low-velocity zone intersected by scrapes left by drifting icebergs on the paleo-seafloor, the gas cloud and the base cretaceous reflector, respectively. These structures have been well documented by FWI in Sirgue et al (2010), Barkved et al (2010), Operto et al (2015), Yang et al (2016a) and Figure 11. FWI perturbation models (Q).…”
Section: Modelssupporting
confidence: 53%
“…The subsurface target is a North Sea oil field in a 70 m depth shallow water environment (Barkved et al 2010;Sirgue et al 2010;Haller et al 2016;Yang et al 2016a). The overburden is characterized by soft sediments in the near surface and a low-velocity gas cloud above the chalk reservoir, which is located at around 2.5 km depth.…”
Section: Study Area and Datamentioning
confidence: 99%
“…But in practice, we always generate extra nonreservoir updates because there are a finite number of iterations used for inverting the baseline model. Watanabe et al (2005), Asnaashari et al (2012), Yang et al (2016), and Kamei and Lumley (2017) use double-difference FWI (DDFWI) to invert for time-lapse velocity changes and show that DDWI provides a more accurate estimate for the time-lapse changes compared with the previously discussed strategies. In this strategy, the estimated baseline model is used as the initial model, but instead of inverting the monitor data as a whole, we invert the time-lapse differences between the baseline and monitor data sets.…”
Section: Workflowmentioning
confidence: 99%
“…Resolution analysis by random probing. Journal of Geophysical Research: Solid Earth 120 (8), 5549-5573. 15 Fichtner, A. and J. Trampert (2011a).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Time-lapse seismic is a widely used tool for the dynamic reservoir monitoring and assessing the reservoir changes due to production [2][3][4]. Recent studies have shown the applicability of the full waveform inversion for the timelapse seismic problem [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%